2014
DOI: 10.1089/aid.2013.0248
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the α4β7Lymphocyte Homing Receptor in HIV-Infected Patients with Distinct Transmission Routes and Disease Progression Profiles

Abstract: The α4β7 is a lymphocyte homing receptor to the gut-associated lymphoid tissue (GALT). HIV-1 gp120 binds to α4β7 integrin through a mimetic tripeptide in V2 and ensures successful infection of GALT. In the present report, we investigated the presence of polymorphisms in the α4β7 cytoplasmic and α4 N-terminal binding domains and their potential association with susceptibility to HIV infection or disease progression. Subjects displaying distinct categories of disease progression or transmission routes (HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[3][4][5][6][7] An ongoing randomized study called the ECHO (Evidence for In our prior study, we showed that altered expression of putative HIV/SIV factors during the luteal phase of the menstrual cycle could contribute to greater risk of vaginal acquisition during this phase. 32 We showed that LNG/EE-based COC use had a similar effect: It depressed antiviral genes like SLPI, 33 and promoted expression of integrins that enhance HIV spread. 32 We showed that LNG/EE-based COC use had a similar effect: It depressed antiviral genes like SLPI, 33 and promoted expression of integrins that enhance HIV spread.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[3][4][5][6][7] An ongoing randomized study called the ECHO (Evidence for In our prior study, we showed that altered expression of putative HIV/SIV factors during the luteal phase of the menstrual cycle could contribute to greater risk of vaginal acquisition during this phase. 32 We showed that LNG/EE-based COC use had a similar effect: It depressed antiviral genes like SLPI, 33 and promoted expression of integrins that enhance HIV spread. 32 We showed that LNG/EE-based COC use had a similar effect: It depressed antiviral genes like SLPI, 33 and promoted expression of integrins that enhance HIV spread.…”
Section: Discussionmentioning
confidence: 86%
“…22 30 In our study, DMPA also enhanced expression of genes like VEGF that have been linked to HIV pathogenesis, 31 and genes from the integrin family including ITGB7, which helps in trafficking and retention of HIV-infected lymphocytes in multiple host sites, thus facilitating viral dissemination. 32 We showed that LNG/EE-based COC use had a similar effect: It depressed antiviral genes like SLPI, 33 and promoted expression of integrins that enhance HIV spread. 34 Additionally, there were genes whose expression was influenced by both, DMPA and LNG: in addition to suppressing expression of a plethora of antiviral serpins, cystatins, β-defensin, and S100A proteins, 14,21 they downregulated cornulin, an epithelial barrier protein that protects the host from viral entry, and upregulated potentially HIV-promoting genes including metalloproteinases and tetraspanins.…”
Section: Discussionmentioning
confidence: 86%
“…The V2 domain of gp120 contains a similar tri-peptide motif at position 179–181 (HXB2 numbering) with the aspartic residue at position 180 being 98% conserved across all HIV isolates [ 3 , 14 ]. The ITGA4 gene that encodes the α4 subunit shows no polymorphisms in humans and did not correlate with HIV transmission or disease progression [ 15 ]. Nevertheless, there appears to be significant variation in the levels of α4β7 reactivity among viruses from different individuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%